On the reform of the complex and plural european model of foreign investment control on national security grounds - Esplugues Mota, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
For less than a decade, the European Union has been forced to modulate its position of openness towards free trade and the free flow of foreign investment. With Regulation 2019/452 as a key element, it has rapidly developed a set of texts that articulate a security response to this complex and polymorphous reality. This pluralist model is characterised by its dynamism and is subject to a process of constant expansion and adaptation, with the planned reform of the mentioned Regulation of 2019 as one of its milestones.
Keywords: foreign direct investments; foreign investment control; foreign investment regulation; common investment policy; new investment regulation